Strategic Issues in Food Production in Sub-Saharan Africa - Mellor, John W.; Delgado, Christopher L.; Blackie, Malcom J. (International Food Policy Research Institute, 1987)
This book starts with the premise that African food problems must and can be solved in large part by increased national food production. That this premise is clearly shared by the political leadership of African nations is demonstrated in numerous public statements at national, regional, and pan-African levels. It is reflected in the 20 contributions in this book by nationals of African countries. Why this view has not been implemented is the subject of several chapters.